COMPARATIVE EVALUATION OF HOMOGENEOUS AND HETEROGENOUS CATALYSTS IN THE ESTERIFICATION OF WASTE COOKING OIL - Ambarwati, Septiana; Hutapea, Henny Parida; Banuwati, Ameilia Wahyu; Fuadah, Fani (LPPM Universitas Duta Bangsa Surakarta, 2025)
Waste cooking oil is a potential raw material for biodiesel production, yet its reuse poses health and environmental risks due to the presence of carcinogenic compounds and high peroxide values. This study aimed to convert waste cooking oil into biodiesel through the transesterification process using different catalysts—acid (HCl), base (NaOH), and heterogeneous (MgO)—combined with pretreatment methods (untreated, bleaching earth, and banana peel adsorption). The reactions were carried out using ethanol as alcohol, followed by homogenization, heating at 60°C for 1 hour, and settling for 24 hours. The results showed that HCl produced the highest biodiesel yield (up to 3.1792 with bleaching earth treatment), followed by MgO and NaOH. Glycerol was obtained as the main by-product, with the highest values also associated with HCl catalysis. Residues were only formed in reactions involving NaOH and MgO due to their heterogeneous and insoluble nature, whereas no residue was found in HCl-based reactions. Pretreatment with bleaching earth significantly improved biodiesel yield compared to banana peel or untreated samples. In conclusion, acid-catalyzed transesterification of pretreated waste cooking oil, particularly with bleaching earth treatment, provides the most effective route for biodiesel production while also generating glycerol as a valuable by-product.